Eksplorasi Efektivitas Flipbook Digital Interaktif terhadap Motivasi dan Keterlibatan Belajar Siswa pada Pembelajaran di Era Digital - Muhammad Kholil; Muhammad Suaidi Ali; Mohammad Hamdan (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2026)
. In the context of education in the digital era, the presence of learning media such as digital flipbooks is an important strategy to increase student motivation and learning engagement. This study aims to explore the effectiveness of using interactive digital flipbooks in increasing student motivation and engagement in the learning process. The use of this media is seen as able to bridge the gap between the needs of students who are familiar with technology and conventional learning methods that tend to be less engaging. This study used a qualitative approach with a case study method on high school students who have used digital flipbooks in learning activities. Data collection techniques were carried out through in-depth interviews, participatory observation, and analysis of learning documents. Data were analyzed thematically to identify patterns of flipbook use, student responses to the media, and their impact on aspects of motivation and learning engagement. The results showed that the use of interactive digital flipbooks had a positive Influence on increasing learning interest, active student involvement during learning, and a deeper understanding of the Material. Attractive visualizations, interactive features, and ease of access made students more enthusiastic about participating in learning. However, challenges were still found in the form of limited device access and teachers’ abilities in designing flipbooks that suit students’ needs. Therefore, ongoing training and technical support are needed to optimize the use of this media. This Research provides a practical contribution to the development of digital learning media that is relevant to the characteristics of today’s generation of learners and supports participatory, innovative, and meaningful learning